TINJAUAN YURIDIS TERHADAP PASAL 27 AYAT (1) UNDANG – UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Sugianto Sugianto (Universitas Kapuas Sintang, 2019)
Efforts to tackle criminal abuse committed by parents of students against teachers that occur in schools both at the high school, junior high school and elementary school level. This aims to find out the efforts made by the school to overcome the persecution of teachers and to find out the factors that cause the persecution of teachers by parents of students, and to know whether a new law is needed to provide protection for teachers and lecturers. . The teachers hope they are given protection in carrying out their duties, the efforts made by the government in preventing both before and after the persecution are not enough to just coordinate and communicate with the teacher or parent council but the most important effort is carried out by all parties namely holding meetings together such as committees, schools, teacher councils, and parents of students in uniting steps to create a dignified and quality education. Teachers are an inseparable part of our current national education system and therefore the work of being a teacher is very noble, teachers are given tasks such as educating, teaching, and fostering students to eradicate poverty and ignorance from all walks of life in order to fight for prosperity in every joint- life joint. Keywords: Efforts, Countermeasures, Persecution, Teachers.